The effects of Rumensin, protein, energy, and post-weaning illness on reproductive performance in replacement heifers - Sprott, L.R.; Kiracofe, G.H.; Corah, L.R.; Riley, Jack G. (Kansas State University. Agricultural Experiment Station, 2011)
Rumensin increased the number of heifers cycling at 394 days of age and tended to decrease the weight at puberty, with no effect on conception or pregnancy. Rumensin also increased average daily gain, total weight change, and feed efficiency. Protein level had no direct effect on reproductive or heifer performance. Heifers on higher energy rations tended to cycle s09ner and be younger and lighter at puberty. Higher energy rations caused faster daily gain, more total weight change, and better feed efficiency. Post-weaning sickness had no effect on reproductive performance or growth.
Keywords: Beef; Protein; Energy; Post-weaning; Reproductive performance; Replacement heifers